Answer:
Formula should be an = 3 + 5(n - 1)
The 12th term = 3 + 5(12 - 1) = 58
Step-by-step explanation:
Let's find the value of the first term using the given formula:-
n = 1 is plugged into the formula:-
a1 = 5 + 3(1- 1)
= 5 + 3(0)
= 5
This gives the wrong value ( it is 3) so the formula is incorrect.
If we study the sequence we see that the common difference is 8-3 = 13 - 8 = 5 and the first term is 3.
The student has confused the first term with the common difference
The correct formula is an = 3 + 5(n - 1)